CAPM estendido para momentos superiores : um teste empírico - Guedes, Ricardo Brito (2011)
The inclusion of higher moments in CAPM has been discussed in recent decades. This work performs an empirical test of the model extended to the third and fourth moments, in which the skewness and kurtosis are also priced. This test was based on Generalized Method of Moments (GMM) procedures, in which all the moment conditions derived from the theoretical model. The data used were the daily returns of the most liquid Brazilian stocks between 2004 and 2006.